(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article sheds light on the current state of economic development in Uzbekistan and its strategic initiatives in attracting foreign investments, developing technological sectors, and modernizing infrastructure. Key directions of economic policy are discussed, such as the development of priority investment projects, digital transformation, and the enhancement of transportation infrastructure.